Resource‐Saving Production of Dialdehyde Cellulose: Optimization of the Process at High Pulp Consistency - Lucia, Arianna (ChemSusChem, 2019)
Oxidation of cellulose with periodate under aqueous conditions yields dialdehyde cellulose, a promising functional cellulose derivative. The main obstacles for this oxidation have been its slow kinetics and the dilute reaction conditions, requiring considerable amounts of water and energy. In this study, these drawbacks are overcome by conducting the oxidation at high cellulosic pulp consistency with a cellulose/water weight ratio of 1:4. The oxidizer, cellulose, and water are efficiently mixed in a ball mill. Oxidation occurs mostly in the subsequent step, during the resting time (no further milling/mixing is required). The reaction and resource efficiency of the process are optimized by experimental design and a maximum aldehyde content of 8 mmol g(−1) is obtained with a periodate/cellulose molar ratio of 1.25, a milling time of 2 min, and a resting time of 8 h. The developed method allows fine tuning of the oxidation level and is a key step towards the sustainable periodate oxidation of cellulose also on larger scale.